Evidence for flavivirus(es) outside of the distribution area for Ixodes ricinus in Norway. - Traavik, T. (Cambridge University Press, 1984)
Small rodent (vole) sera were collected from three different locations in Norway. One of these was within the distribution area for Ixodes ricinus, and a tick-borne encephalitis (TBE) virus strain had been isolated from ticks collected there (Traavik & Mehl, 1977). The two other locations were outside the I. ricinus area, one in southern Norway, the other at nearly 70 degrees N. The sera were tested for TBE antibodies by hemagglutination inhibition (HI), hemolysis-in-gel (HIG) and complement fixation (CFT). All sera were also tested for HI antibodies to Uukuniemi (UUK) virus, and some positive TBE HI reactions were verified by separation of immunoglobulins and serum lipoproteins in NaBr gradients. Animals containing TBE virus antibodies reacting in all three serological tests and animals with UUK HI antibodies were detected only from the location within the I. ricinus area. From the two locations outside the I. ricinus area we found animals which had antibodies reacting with TBE virus in HI and HIG, but not in CFT. Antibodies to UUK were not detected. The results indicate that flavivirus(es) related to, but not identical with TBE viruses are transmitted by other vectors than I. ricinus in parts of Norway.